Edukasi Keamanan Siber Berdigital dengan Aman - Surbakti, Feliks Prasepta Sejahtera (Prima Abdika: Jurnal Pengabdian Masyarakat, 2024)
The rapid development of digital technology in Indonesia has heightened the need for cybersecurity education to safeguard individuals against prevalent digital fraud. This community service initiative, titled "Cybersecurity: Safe Digital Practices," aims to raise awareness and educate participants about key aspects of digital security. The program covers the fundamentals of cybersecurity, including digital fraud detection, device security, identity protection, and understanding digital footprints. The implementation involved interactive workshops that addressed common cyber threats and equipped participants with practical strategies for safe digital engagement. Methodologies included presentations on real-life cyber-attack cases, discussions on digital fraud tactics such as phishing, pharming, and sniffing, and hands-on sessions for using security tools like two-factor authentication, fingerprint authentication, and device tracking. Participants were encouraged to engage actively, allowing for the immediate application of learned strategies. Results indicate an increased awareness and capability among participants to recognize and counteract digital fraud. Through post-program evaluations, participants reported a significant improvement in their confidence and ability to protect personal information and secure digital devices. In conclusion, this program effectively enhanced the cybersecurity skills of the participants. It is recommended that future programs expand to include more advanced topics, such as cybersecurity for small businesses and data privacy laws. Continued collaboration with educational institutions and community organizations can further disseminate cybersecurity knowledge across broader demographics, ensuring safer digital practices at the community level.